Serum uric acid level predicts the progression of amyotrophic lateral sclerosis following treatment with edaravone. (31st December 2022) - Han, Hee Jo; Shin, Ha Young; Choi, Young-Chul; Kim, Seung Min; Kim, Seung Woo
ABSTRACT : Introduction: Uric acid and edaravone might exert a neuroprotective effect in amyotrophic lateral sclerosis (ALS) by reducing oxidative stress. We analyzed whether the treatment effect of edaravone is pronounced in patients whose uric acid level increased after the treatment with edaravone. Materials and methods: Forty patients with ALS who underwent treatment with edaravone were included. Baseline uric acid level and the rate of decline in uric acid after edaravone treatment were recorded. The rate of change of ALS functional rating scale-revised (ΔALSFRS-R/month) was calculated based on baseline ALSFRS-R score and ALSFRS-R score 6–24 weeks after the treatment. Results: The serum uric acid levels decreased after treatment in 26 (65%) patients and increased in 12 (30%) patients. The ΔALSFRS-R/month was significantly faster in patients whose uric acid decreased (median 1.5 [Q1–Q3, 0.7–3.1]) than in patients whose uric acid increased (0.2 [0–1.0], p = 0.021). A high baseline uric acid level and low rate of decline in uric acid was associated with slower disease progression after adjusting for age, initial symptoms, and riluzole administration ( p = 0.030 and p = 0.041, respectively). Discussion: High baseline values and low rate of decline in uric acid may predict slow disease progression in ALS patients treated with edaravone.